1998
DOI: 10.1152/ajprenal.1998.275.5.f777
|View full text |Cite
|
Sign up to set email alerts
|

Dietary lipids regulate β-oxidation enzyme gene expression in the developing rat kidney

Abstract: This study examines the ability of dietary lipids to regulate gene expression of mitochondrial and peroxisomal fatty acid β-oxidation enzymes in the kidney cortex and medulla of 3-wk-old rats and evaluates the role of glucagon or of the α-isoform of peroxisome proliferator-activated receptor (PPARα) in mediating β-oxidation enzyme gene regulation in the immature kidney. The long-chain (LCAD) and medium-chain acyl-CoA dehydrogenases (MCAD) and acyl-CoA oxidase (ACO) mRNA levels were found coordinately upregulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
45
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(46 citation statements)
references
References 32 publications
1
45
0
Order By: Relevance
“…3 are involved in lipid metabolism, and have previously been shown to be regulated by PPAR agonists. These genes include bifunctional enzyme (peroxisomal -oxidation) (Bardot et al 1993), Cyp4A10 (microsomal -hydroxylation) (Bell et al 1993), acetyl-CoA C-acetyltransferase (mitochondrial -oxidation) (Gould-Rothberg et al 2001), beta-ketothiolase (mitochondrial -oxidation), longchain-acyl-CoA dehydrogenase (mitochondrial -oxidation) (Ouali et al 1998), and long-chainfatty-acyl-CoA synthetase (fatty acid activation) (Schoonjans et al 1995). The regulation of HMG-CoA-synthase (ketone body synthesis) (Rodriguez et al 1994) has also been described previously.…”
Section: Discussionmentioning
confidence: 99%
“…3 are involved in lipid metabolism, and have previously been shown to be regulated by PPAR agonists. These genes include bifunctional enzyme (peroxisomal -oxidation) (Bardot et al 1993), Cyp4A10 (microsomal -hydroxylation) (Bell et al 1993), acetyl-CoA C-acetyltransferase (mitochondrial -oxidation) (Gould-Rothberg et al 2001), beta-ketothiolase (mitochondrial -oxidation), longchain-acyl-CoA dehydrogenase (mitochondrial -oxidation) (Ouali et al 1998), and long-chainfatty-acyl-CoA synthetase (fatty acid activation) (Schoonjans et al 1995). The regulation of HMG-CoA-synthase (ketone body synthesis) (Rodriguez et al 1994) has also been described previously.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding PPAR-α, it is known to be involved in the control of fatty acid β-oxidation (4,5). PPAR-α is also reported to regulate cytochrome P450 4A genes through their PPRE at proximal tubules in the kidney (4,25), and may regulate sodium metabolism (4) and blood pressure (26).…”
Section: Fig 6 Immunohistochemical Analyses Using Anti-ppar Antibodmentioning
confidence: 99%
“…There are 3 known isoforms of PPARs, PPAR-α, Recently, several studies have suggested the functional significance of PPARs in renal pathophysiology (4). It is assumed that PPAR-α is involved in the control of fatty acid β-oxidation and the regulation of cytochrome P450 4A genes in the kidney (4,5), and this isoform may affect sodium retention (4). Moreover, Kamijo et al recently demonstrated that PPAR-α in the proximal tubules was involved in the maintenance of ATP homeostasis to degrade absorbed proteins (6).…”
Section: Introductionmentioning
confidence: 99%
“…The mitochondrial enzyme cDNA probes used in this study were rat MCAD EcoRI fragment of 871 bp (13) and rat LCAD EcoRI fragment of 1200 bp (14). A 559-bp ACO cDNA (15) and a 717-bp cDNA comprising part of the D and E domains of the rat PPAR␣ (16) were obtained by reverse transcription coupled to PCR as described elsewhere (17). For FATP, the hybridization was performed with the 1.3-kb BamH1-BglII fragment of mouse cDNA (9).…”
Section: Northern Blot Analysismentioning
confidence: 99%